Analisa pengaruh variasi kuat arus, media pendingin, dan merk elektroda terhadap kekuatan tarik dan distorsi sudut sambungan baja st 37 - Hesti Istiqlaliyah; Am Mufarrih (Jurnal Teknik Mesin Indonesia, 2016)
The purpose of this research is to know the influence of variation of current strength, cooling medium, and brand of electrode to tensile strength and distortion connection angle of st 37. SMAW welding using E6013 electrode having 2 mm diameter. The test specimens use st 37 plate with a thickness of 5 mm. Furthermore, distortion testing and tensile tests were performed. In determining the result of the variance of tensile strength and distortion, the experimental design of the Taguchi method is used. The tensile strength response characteristic is the larger is better, while the distortion response characteristics are the smaller is better. The results showed that the optimum condition for tensile strength was a factor of A strong current at level 2 of 65 ampere, C brand factor electrode at level 2 using brand RB electrode, while cooling factor B at level 2 using water type refrigerant. While the optimum condition for the distortion response of factor B cooler with level 2 using air conditioner, brand C factor electrode using RB brand electrode, and factor A strong current level 2 using 65 ampere. Based on ANOVA, the two responses of these three factors have no significant effect on the response.